FAKTOR-FAKTOR PENYEBAB KEPUNAHAN BAHASA DAERAH DI TANAH RANTAU - Atri Dewi Azis; Mahyuni Mahyuni; Syahdan Syahdan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
Language is one means of communication to interact each other. In social interaction has become the inevitability of influence each other among the languages spoken The language that the majority used will survive and limited the space of other languages that are rarely used by speakers. Therefore, the purpose of this study is to analyze the causal factor of regional language death and provide description about condition of the use of regional language on overseas lands with limited to Bugis language (BB) in Lombok. The research was conducted from March until October 2017 in Labuhan Haji East Lombok. The consideration of the choice of research location is based on geographical area which is one of the areas inhabited by many native Bugis speakers from South Sulawesi. The finding of the research shows that Bugis language as Bugis interpersonal interaction language in Lombok is still spoken by them. However, finding the native speakers is like a needle in a haystack. It means that Bugis language is very difficult to find inL ombok. Regional languages can continue to live and grow by making them berprestise by encouraging all family to use the regional language as the first language to communicate in the family